Fly Ash Proppant Developed for Hydraulic Fracturing - Haydar, Raz Rzgar (AUC Knowledge Fountain, 2026)
Proppants are critical components in hydraulic fracturing, used to maintain fracture conductivity and enhance reservoir stimulation. In high-pressure and harsh reservoir environments, the use of high-strength proppants is essential to ensure well performance. Conventional proppants, being sand, ceramic, and sintered bauxite can be expensive, and their use often requires costly fracture fluids. This study investigates the possibility of utalizing fly ash geopolymers as a sustainable alternative that is also cost-effective for proppants manufacturing. Fly ash, a by-product from the combustion of coal and other materials, was explored as a base material for proppants, utilizing an alkaline solution as an activator and binder. The research aims to develop fly ash-based proppants that meet the stringent mechanical, environmental, and cost performance standards required in hydraulic fracturing applications. The fly ash proppant samples were subjected to a variety of tests to evaluate their physical and mechanical properties. Density measurements showed that the fly ash-based proppants exhibited significantly lower densities (ranging from 1.09 to 1.36 g/cm³) compared to conventional materials like sand (1.5–1.6 g/cm³) and sintered bauxite (3.5 g/cm³). The lower density of the fly ash proppants contributes to improved buoyancy, enhancing their transport within fracturing fluids and facilitating more effective proppant placement in fractures. This characteristic aligns with the goal of achieving a lightweight proppant that requires less viscous fracture fluid, thereby reducing overall costs. The proppant samples were also tested for their environmental durability, with exposure to high temperatures, pressures, acidic, saline, and crude oil environments. The results revealed notable variations in the proppants' performance based on their mix designs. The B20W25 mix design demonstrated the best durability, exhibiting minimal surface erosion, cracking, and weight loss across various environmental conditions. In contrast, the B25W25 mix showed significant degradation, particularly under high-pressure and high-temperature conditions, highlighting the critical role of mix design in ensuring proppant performance. The B22W25 mix, while performing moderately well, was found to be more susceptible to high-alkalinity conditions compared to the B20W25 mix. Compressive strength testing revealed that the B20W25 mix exhibited the highest strength among the fly ash-based samples, with a compressive strength of 8144 KPa (1181.19 psi). The B25W25 mix, however, demonstrated lower compressive strength and failed more readily under environmental stresses. These results highlight the critical role of optimizing binder content and the water-to-binder ratio in improving the strength and durability of fly ash-based proppants. Additionally, the study compared the performance of volcanic ash-based geopolymers, which outperformed the fly ash-based samples in compressive strength, with the B10W30 volcanic ash mix reaching a compressive strength of 13,988 KPa (2028.79 psi), suggesting volcanic ash as a promising alternative material for proppant development. Incorporating sand into fly ash-based geopolymer mixes was also investigated, showing that moderate sand content (25%) improved compressive strength, while higher sand content (50%) led to a reduction in strength due to increased porosity. The study highlights the importance of carefully balancing binder and filler content to optimize the mechanical properties of fly ash-based proppants. Overall, the findings of this research suggest that fly ash-based proppants hold significant potential as a cost-effective, sustainable alternative to conventional materials used in hydraulic fracturing. Despite their lower compressive strength compared to traditional proppants, fly ash-based proppants offer advantages such as reduced material costs, enhanced buoyancy, and environmental sustainability. Future research should focus on optimizing the mix designs, binder-to-filler ratios, and further improving the mechanical properties of fly ash-based proppants to meet the demanding requirements of high-pressure, high-temperature, and chemically aggressive environments typical in deep-well hydraulic fracturing applications.